Experience, Knowledge, and Preparedness as Predictors of Disaster Response Priorities: Perspectives of Nursing Students - Muhammad Muhammad; Sofyan Sufri; Nurhayati Syukri; Yeni Rimadeni (Poltekkes Kemenkes Aceh, 2026)
Background: Effective disaster response requires healthcare workers to prioritize appropriate actions in emergency situations. For nursing students, experience, disaster-related knowledge, and preparedness are considered essential competencies; however, evidence regarding their relationship to disaster response prioritization is limited. Purpose: To analyze the factors of experience, knowledge, and preparedness as predictors for determining disaster response priorities among nursing students. Methods: This cross-sectional, observational, analytical study involved 73 final-semester Diploma Three Nursing students selected using a total sampling technique. Data were collected using a modified disaster preparedness perception questionnaire to measure experience, knowledge, preparedness, and disaster response priorities. Data analysis was conducted using descriptive statistics, heat map visualization, and ordinal logistic regression. Results: The results of ordinal logistic regression indicate that knowledge of social disasters is the strongest predictor of students' disaster response priorities (β < 0; p < 0.05). Greater knowledge of social disasters is associated with students' tendency to actively assist victims rather than simply following the directions of formal authorities. Knowledge of non-natural disasters also contributes to response priorities, but the correlation is weaker. Disaster experience and general preparedness do not show a statistically significant relationship with disaster response priorities. Conclusion: Specific knowledge of disaster types plays a greater role in determining students' response priorities than direct experience and general preparedness. Strengthening disaster education needs to emphasize the characteristics, risks, and response measures for each type of disaster through contextual, inclusive, and simulation-based learning.